Perencanaan Arsitektur Sistem Informasi Menggunakan Togaf Adm Pada Kantor Desa Simpang Terusan Dengan Evaluasi Ea-Scorecard - Rani Oktavia, Feby; Rasywir, Errissya; Aryani, Lies (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2024)
The Simpang Terusan Village Office is one of the government agencies tasked with carrying out Village Government activities, community empowerment, serving the community and maintaining public service infrastructure and facilities as well as fostering community institutions at the village level. The Simpang Terusan Village Office, apparently, does not yet have a mature enterprise architecture plan and has the desire to have an Enterprise Architecture. Without an information system strategic plan or mature Enterprise Architecture, the application of IS/IT at the Simpang Terusan Village Office will have an impact on less than optimal services provided to the community. This study aims to make an enterprise architecture plan using TOGAF ADM and test the information system architecture plan using an enterprise architecture score-card to find out whether the EA design that has been made is valid enough, so testing is needed. The research method in collecting data is to conduct interviews, observation, and document analysis. research results are made into research reports that can provide a complete picture of the system being built or the results of information system architecture planning using the designed TOGAF ADM, produce a blueprint as a guide for building an integrated information system consisting of 13 proposed applications and enterprise architecture planning that has been tested for feasibility using the EA-Scorecard method for each score calculation, namely business architecture 69%, data architecture 57%, application architecture 52%, technology architecture 61%. It can be stated that the recommendations for enterprise architecture planning at the Simpang Terusan Village Office are declared valid.